Sliding-Mode Control of a Dc/Dc Postfilter for Ripple Reduction and Efficiency Improvement in POL Applications - S. I. Serna-Garcés; R. E. Jiménez; C. A. Ramos-Paja (Journal of Applied Mathematics)
This paper proposes an active postfilter based on two Buck converters, connected in parallel, operating in complementary interleaving. In such a configuration the ripple in the load current could be virtually eliminated to improve the power quality in comparison with classical Point-Of-Load (POL) regulators based on a single Buck converter. The postfilter is designed to isolate the load from the main Buck regulator, leading to the proposed three-converter structure named BuckPS. The correct operation of the postfilter is ensured by means of a sliding-mode controller. Finally, the proposed solution significantly reduces the current harmonics injected into the load, and at the same time, it improves the overall electrical efficiency. Such characteristics are demonstrated by means of analytical results and illustrated using numerical results.